The standard answer `0*0 = 0`

is fine for most people. But the odd person who found this page will probably have second thoughts about it. As a philosoper you may feel that ‘zero times nothing’ is even less than plain empty: a deeper void.

Shouldn’t we express this as a power `0^2`

in mathematics? Or will all positive powers of zero necessarily collapse to `0`

under the usual assumptions in arithmetic? Can’t we make an exception so that zero powers make sense?

You have to ask yourself: what is zero? There are two simple answers.

First answer is the **+0** axiom that `a+0 = a`

. The function of adding zero to a number is not to change that number. This is called the identity element of addition in field theory.

Second answer is that zero is defined as one, minus one. The **1-** axiom substitutes a sign for a counted down entry `1- := 0`

in my natural array system, where a number increments by unit `1`

and the unit `-`

decrements it.

Equality `X=Y`

implies `Y=X`

(a symmetry relation), but in substitution the right side replaces the left (not symmetric).

Under the usual field rules we have:

`0*0 = 0*0 + 0 = 0*0 + 1*0 = (0+1)*0 = 1*0 = 0`

.

Using the **+0** axiom, symmetry of equality, the identity element of multiplication `1*a = a`

and the distributive law `(a+b)*c = a*c + b*c`

.

By induction this reduces `0^n = 0`

for all `n>0`

in standard algebra.

If we’d like to maintain that `0*0`

is somehow different from plain `0`

, some exceptions must be introduced to the axioms of field theory. Simplest is not to let our **+0** axiom apply to powers of zero. In turn we can discard the exception that there is no multiplicative inverse `1/0`

and allow for negative powers of zero too.

Try on this zero division ring. If `0^-1 = 1.. = ω`

continues to make sense, your arithmetical system just became rich!

With my **1-** substitution axiom an expression with just zero values like `0*0`

defies reduction altogether.

`1- + -*0 = 1 + -*1 + -*0 = 1 + -*(1+0) = 1 + -*1 = 1- := 0`

.

`1- + -*0 := 0 + -*0 = 1*0 + -*0 = 1-*0 := 0*0`

.

One way substitution to define inverses, how can we cope?

I can’t prove that `0+0 := 0`

either, should I leave it, or make it a new rule?

`1- + 0 := 0 + 0 = 0*1 + 0*1 = 0*(1+1) = 0*2`

.

`1- + 0 = 1 + -*1 + 0 = 1 + 0 + -*1 = 1 + -*1 = 1- := 0`

.

To hold on to zero powers I maintain that `-*0 ≠ 0`

and take `-*-`

to be a double negated variation of `1`

that also may raise special powers.

Some 10 years ago on my xs4all blog I wrote a series of articles, where I derived theorems from such a contrived substitution axiom. But I am sceptical now. To drive the rule of additive inverses into a one way street raises a serious obstruction in the centre of mathematics.

What do you think?

Dat ziet er goed uit! Nu wachten op reacties!

Kusjes Wattson

PS Mag ik hem “liken”?

LikeLike

Je bent geabonneerd zeker? Ik was net aan het schrijven, maar Like! maar Wattson 😉

LikeLike